Infantile Thiamine Deficiency and Language Impairment - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Developmental language impairment in 59 children, aged 5-7 years, exposed to a thiamine deficiency in defective milk formula fed during the first year of life is studied by researchers at Tel Aviv University and Sourasky Medical Centre, Israel.